Women’s knowledge on Cytomegalovirus infection and prophylactic measures in the light of own research - Wasik, Magdalena Anna (Journal of Education, Health and Sport, 2019)
Introduction: Recently an increasing number of infections caused by Cytomegalovirus (CMV) have been observed worldwide. A human being is the reservoir of the infection. The infected person releases viruses in saliva, tears, semen and urine. Pregnant women, newborns, AIDS patients and immunocompromised persons are the most exposed to the severe clinical course of the infection. Preventive measures play an important role in limiting the spread of CMV infections. Aim of the study: The aim of the study was to investigate the knowledge of women about Cytomegalovirus infection and preventive actions taking into account variables such as age, education and number of children. Material and method: The study was conducted in the period from February to June 2016 by means of a diagnostic survey. 63 women aged 20 and over took part in the survey. The tool used in the study was a questionnaire. The most numerous group were the respondents aged 20-29 years and the least aged 40-49 years. The research results were developed in Microsoft Excel and Statistica 13.1. Results: The data analysis shows that women with higher and secondary education have greater knowledge about Cytomegalovirus than women with vocational education. Conclusions: The level of knowledge of women about Cytomegalovirus infection varies according to the education of the women who have undergone the study. It is extremely important to disseminate knowledge about the prophylactic measures that can significantly affect the proper development of the foetus.